1977
DOI: 10.1007/bf01219709
|View full text |Cite
|
Sign up to set email alerts
|

B1-3,5-diiodotyrosine insulin: A valid tracer for insulin

Abstract: Insulin, specifically substituted at the PheB1 position with 3,5-diiodotyrosine, has been tested in several biological and immunological systems. Immunoreactivity was assessed using antisera specific for different parts of the insulin molecule. Biological activity in vitro was estimated on isolated rat fat cells. In vivo bioactivity (hypoglycaemia) and metabolism (metabolic and urinary clearance rates, half-life, apparent distribution space) were measured by infusion of the material into greyhounds. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The potency of B 1 acetoacetyl insulin was 85 per cent relative to insulin, comparable to reported values for B 1 succinyl andBt acetyl insulins [5]. Replacement of the B 1 residue with diiodotyrosine did not reduce bioactivity as we have reported elsewhere [29]. A1, Table 3.…”
Section: Isolated Fat Cell Assayssupporting
confidence: 89%
See 1 more Smart Citation
“…The potency of B 1 acetoacetyl insulin was 85 per cent relative to insulin, comparable to reported values for B 1 succinyl andBt acetyl insulins [5]. Replacement of the B 1 residue with diiodotyrosine did not reduce bioactivity as we have reported elsewhere [29]. A1, Table 3.…”
Section: Isolated Fat Cell Assayssupporting
confidence: 89%
“…with a radioactive residue should produce a fully active derivative and hence a valid tracer for studies on insulin action and metabolism, as shown for Bt-3,5-diiodotyr. Insulin [29]. Similarly, the observations [9] that the greater activity of A1, B29 modified insulins in vivo than in vitro could be explained by their reduced susceptibility to degradation might suggest a therapeutic use for the materials, either as longer-acting forms of the hormone or possibly as potentiators of insulin action through an ability to inhibit degradation of the native hormone.…”
Section: Discussionmentioning
confidence: 92%
“…Both analogues are also full agonists. In addition the reduction of MCR is commensurate with the reduction of lipogenesis potency and conforms to the general relationship noted with a wide range of chemically-modified insulins which includes insulin analogues with single amino acid alterations in the A chain [12] and analogues with modifications at the N terrninus of the B chain, the N terminus of the A chain and the C terminus of the B chain [18,[24][25][26]. At none of these sites are the modifications thought to interfere either with demerisation or with the ability to induce negative cooperative effects.…”
Section: Discussionmentioning
confidence: 99%